The impact of sustainability reporting on dedicated and transient institutional ownership: Evidence from Malaysia - Abd Mutalib, Hafizah; Muhammad Jamil, Che Zuriana; Wan Hussin, Wan Nordin (American Scientific Publishers, 2015)
Investment philosophy that centers on environmental, social and governance issues has gained traction in recent years.The purpose of this study is to examine if sustainability reporting exerts different impact on the share ownership of dedicated and transient institutional investors in a developing market.Using Malaysian setting, a total of 285 firms listed on Bursa Malaysia in the years 2010 and 2011 are selected for this study, which utilizes a one-year lag data for sustainability reporting and contemporaneous data for institutional ownership.The results reveal that sustainability reporting has a positive impact on ownership by dedicated institutions but no impact on the ownership by transient institutions.Further analysis reveals that sustainability reporting exerts positive impact on the ownership of all three types of government-controlled dedicated institutions, namely government-managed pension funds, government-managed unit trust funds and government-managed pilgrims fund, but no impact on the ownership of all three types of private-controlled transient institutions, namely banks, private-managed mutual funds and insurance companies.